Effect of supplementation frequency on intake, behavior and performance in beef steers grazing Marandu grass - Morais, J. A. S. [UNESP]; Queiroz, M. F. S. [UNESP]; Keli, A.; Vega, A.; Fiorentini, G. [UNESP]; Canesin, R. C. [UNESP]; Reis, R. A. [UNESP]; Berchielli, Telma Teresinha [UNESP] (Elsevier B.V., 2014)
Eighteen Nellore steers, with an average initial body weight (BW) of 312 +/- 10.6 kg, grazing Brachiaria brizantha cv. Marandu were assigned to three experimental treatments consisting of different supplementation frequencies (daily [DAI], Monday through Friday [M-F] and Monday, Wednesday and Friday [MWF]). The supplement was offered at a rate of 35.0 g kg(-1) BW per week and contained 565 g kg(-1) corn gluten meal-60, 235 g kg(-1) dry sugarcane yeast, 140 g kg(-1) citric pulp and 60 g kg(-1) mineral premix. Animal performance (ADG), dry matter (DM) intake, DM digestibility, daily grazing time and pattern of supplement intake were evaluated in the steers from February to May. The forage DM intake was estimated using the alkane pair C-32:C-33 and the DM apparent digestibility using the alkane C-35 as an internal marker. A reduction in supplementation frequency did not affect animal performance, with an average weight gain of 0.69 kg/d. Supplementation frequency did not affect (P>0.05) forage and total (forage + supplement) DM intakes or DM digestibility. However, forage and total DM intakes and DM apparent digestibility decreased significantly (P<0.01) from March to May, whereas grazing time during the day (from 06:00 h to 18:00 h) increased by 22% in the same period. The animals receiving infrequent supplementation (M-F and MWF) spent a greater portion of the day grazing when not given the supplement compared to days on which they received the supplement. Reducing the frequency of supplementation from 7 to 3d per week is a viable method to reduce labor and equipment utilization costs as this reduction did not affect intake, digestibility or animal performance in the present study. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Alkanes; Digestibility; Diurnal grazing time; Nellore steer; Supplementation strategies; tropical grass